The effect of mobile phone addiction on sleep procrastination in adolescents: The longitudinal mediating role of physical activity behavior - Wanbin Yu; Xielin Zhou; Bo Li; Jianjun Huang (PLoS ONE, 2025)
Purpose This study explores the impact of adolescent mobile phone addiction on sleep delay and analyzes the longitudinal mediating role of physical activity behavior. It provides a reference for cultivating good habits and healthy behaviors among adolescents. Methods The study was based on the theory of planned behavior and used the Mobile Phone Addiction Scale (MPA), the Bedtime Procrastination Scale (BPS), and the Physical Activity Rating Scale to conduct a longitudinal follow-up survey of 376 healthy high school students in S Province. The survey was conducted three times at intervals of three months, and the data were processed using SPSS and AMOS. Results (1) There is a positive correlation between mobile phone addiction and sleep delay (p < 0.01), and a negative correlation between mobile phone addiction, sleep delay, and physical activity (p < 0.01). (2) T1 mobile phone addiction significantly and negatively predicts T2 physical exercise behavior (β = −0.21, p < 0.001), T1 physical exercise behavior significantly and negatively predicts T2 sleep delay (β = −0.24, p < 0.001), and T1 mobile phone addiction significantly and positively predicts T2 sleep delay (β = 0.25, p < 0.001); T2 mobile phone addiction significantly and negatively predicts T 3 physical activity behavior (β = −0.27, p < 0.001), T2 physical activity behavior significantly negatively predicts T3 sleep delay (β = −0.37, p < 0.001), and T2 mobile phone addiction significantly positively predicts T3 sleep delay (β = 0.24, p < 0.001). (3) The direct effect of mobile phone addiction on physical exercise behavior is 0.08, with a confidence interval of [0.034, 0.153], indicating that the direct effect is established. The longitudinal mediating effect of sleep delay in mobile phone addiction and physical exercise behavior is 0.051, with a confidence interval of [0.02, 0.098], indicating that the longitudinal mediating effect is established. Conclusion (1) There is a two-way correlation between adolescent mobile phone addiction, physical activity behavior, and sleep delay. (2) Adolescent mobile phone addiction can directly affect sleep delay across time and can also indirectly affect sleep delay across time through physical activity behavior.